2002
DOI: 10.1093/chemse/27.3.207
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Pheromone Receptor Gene Is Expressed in Two Distinct Olfactory Organs in Goats

Abstract: Mammals possess two anatomically and functionally distinct olfactory systems. The olfactory epithelium (OE) detects volatile odorants, while the vomeronasal organ (VNO) detects pheromones that elicit innate reproductive and social behavior within a species. In rodent VNO, three multigene families that encode the putative pheromone receptors, V1Rs, V2Rs and V3Rs, have been expressed. We have identified the V1R homologue genes from goat genomic DNA (gV1R genes). Deduced amino acid sequences of gV1R genes show 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 20 publications
1
64
0
1
Order By: Relevance
“…Second, in comparison to the V1R gene repertoire, the V2R repertoire is frequently lost in terrestrial vertebrates (Fig. 1) (Wakabayashi et al 2002). A recent study identified two types of vomeronasal systems in mammals (Takigami et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Second, in comparison to the V1R gene repertoire, the V2R repertoire is frequently lost in terrestrial vertebrates (Fig. 1) (Wakabayashi et al 2002). A recent study identified two types of vomeronasal systems in mammals (Takigami et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This explanation also seems unlikely, because all V2Rs we identified from dogs and cows were pseudogenes (data not shown). Furthermore, all V2R genes identified from the human and goat genomes are pseudogenes (17). In fact, no functional V2Rs have been reported in nonrodent mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a goat V1R gene is known to be expressed in the olfactory epithelium (17). Before we can determine the effects of gene loss in V1R superfamily evolution, we must understand the functional difference between family groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50 intact V2R genes were identified from the mouse and rat genomes , whereas no intact V2R genes were found from the human genome (Bjarnadottir et al 2005) and all the V2R genes identified from goats were pseudogenes (Wakabayashi et al 2002). It is therefore possible that the numbers of functional V2R genes in non-rodent placental mammals are quite small.…”
Section: Vomeronasal Receptorsmentioning
confidence: 99%